QUALITY OF AGED AND TENDERIZED BEEF COMMERCIALIZED IN THE DRACENA REGION, SP - Bosco, D. M. S. [UNESP]; Andrighetto, C. [UNESP]; Luz, P. A. C. [UNESP]; Poiatti, M. L. [UNESP]; Jorge, A. M. [UNESP]; Francisco, C. L. [UNESP]; Aranha, H. S. [UNESP]; Trivelin, G. A. [UNESP]; Vaz, R. F. [UNESP]; Santos, J. M. F. [UNESP] (Inst Zootecnia, 2016)
The objective of this study was to evaluate the physical and microbiological characteristics of aged and tenderized beef commercialized in the Dracena region, SP. Eight samples of aged meat and eight samples of tenderized meat were randomly purchased from commercial establishments and submitted to measurements of pH, shear force, cooking losses and color and to microbiological analysis. A completely randomized design consisting of two treatments and eight replicates was used. Among the physical characteristics studied, significant differences between the tenderization processes were observed for pH, cooking loss, redness (a*), yellowness (b*) and oxymyoglobin/metmyoglobin ratio (O/M) (P< 0.05), with aged meat exhibiting a lower pH and cooking losses and higher a*, b* and O/M values. There were no significant differences (P> 0.05) in shear force or lightness between processes. Microbiological analysis revealed a significant difference (P< 0.05) in total bacterial count and psychotropic count between processes, while there was no difference in the number of enterobacteria (P> 0.05) Despite clear and perceptible differences to the human eye in some physical characteristics, aged and tenderized beef commercialized in the Dracena region, SP, is similar in terms of tenderness and its color and microbiological quality meet the standards required for sale and human consumption.
Keywords: bacterial count; Longissimus; meat tenderization; shear force